PERENCANAAN PEMBANGUNAN PARTISIPATIF BERBASIS NILAINILAI LOKAL DI KELURAHAN LAMBUANG BUKIK, KOTA PADANG - Tamrin Tamrin; Didi Rahmadi; Zulfadli Zulfadli; Asrinaldi Asrinaldi; Aidinil Zetra (Jurnal Pengabdian Warta Andalas, 2018)
There has been an attempt to accommodate the aspirations of the people in developmentplanning through a tiered process, such as the implementation of Musrembang starting from theKelurahan level. However, not all of the aspirations of the community can be channeled through theofficial mechanisms implemented in this government development plan, another channel is needed sothat the aspirations of the unpardonable community in the implementation of Musrembang in Kelurahancan be channeled through other channels outside the government based on local values . Communityservice in Lambuang Bukik urban village, Pauh subdistrict, Padang City is trying to improve the formof development planning based on local values of the community, so that the aspirations of thecommunity that is channeled in the implementation of Musrembang Kelurahan is not only the workprogram of SKPD Kelurahan or other SKPD government agencies but can also be work programs thatcan be funded by community empowerment activities. Through the use of SWOT analysis and adultlearning cycle method and experience, the community participation level in developing developmentplanning and increasing knowledge in formulating the form of community participation planning inLambuang Bukik village, Pauh sub-district, Padang city.